A European, Observational, Prospective Trial of Trabectedin Plus Pegylated Liposomal Doxorubicin in Patients with Platinum‐Sensitive Ovarian Cancer. (3rd January 2021) - Pignata, Sandro; Scambia, Giovanni; Villanucci, Alessandro; Naglieri, Emanuele; Ibarbia, Mikel Arruti; Brusa, Federica; Bourgeois, Hugues; Sorio, Roberto; Casado, Antonio; Reichert, Dietmar; Dopchie, Catherine; De Rivas, Beatriz; et al.
Abstract: Purpose: The noninterventional, prospective NIMES‐ROC phase IV study (NCT02825420) evaluated trabectedin plus pegylated liposomal doxorubicin (PLD) in real‐life clinical practice. Patients and Methods: Eligible participants included adults with platinum‐sensitive recurrent ovarian cancer (PS‐ROC) who had received one or more cycles of trabectedin/PLD before inclusion according to the marketing authorization. The primary endpoint was progression‐free survival (PFS) according to investigator criteria. Results: Two hundred eighteen patients from five European countries were evaluated, 72.5% of whom were pretreated with at least two prior chemotherapy lines and received a median of six cycles of trabectedin/PLD (range: 1–24). Median PFS was 9.46 months (95% confidence interval [CI], 7.9–10.9), and median overall survival (OS) was 23.56 months (95% CI, 18.1–34.1). Patients not pretreated with an antiangiogenic drug obtained larger median PFS ( p < .007) and OS ( p < .048), largely owning to differences between the two populations. Twenty‐four patients (11.0%) had a complete response, and 57 patients (26.1%) achieved a partial response for an objective response rate (ORR) of 37.2%. Fifty‐nine patients (27.1%) had disease stabilization for a disease control rate of 64.2%. No statistically significant difference in PFS, OS, or ORR was observed by BRCA1 / 2 status and platinum sensitivity. Most common grade 3/4 adverse events (AEs) were neutropenia (30.3%), anemia (6.4%), thrombocytopenia (5.5%), and asthenia (5.0%). No deaths attributed to treatment‐related AEs or unexpected AEs occurred. Conclusion: The combination of trabectedin/PLD represents a clinically meaningful and safe option for patients with PS‐ROC regardless of prior treatment with an antiangiogenic drug, being comparable with previously observed outcomes in selected and less pretreated patients from clinical trials. Implications for Practice: This noninterventional, prospective study, conducted in 57 reference sites across Europe, consistently confirmed that trabectedin plus pegylated liposomal doxorubicin (PLD) in routine clinical practice represents a clinically meaningful and safe option for women with platinum‐sensitive recurrent ovarian cancer. Although the study population represented a heterogeneous, older, and more pretreated population than those in prospective clinical trials, the combination of trabectedin plus PLD induced comparable clinical benefits, with a similar and manageable safety profile. Overall, these findings show that trabectedin in combination with PLD maintains antitumor activity when administered to heavily pretreated patients in real‐life clinical practice. Abstract : This clinical trial evaluated the use of trabectedin plus pegylated liposomal doxorubicin (PLD) in patients with platinum‐sensitive recurrent ovarian cancer and its efficacy and safety in routine clinical practice in five European countries.